2014
DOI: 10.1136/gutjnl-2013-306518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of inflammatory mediators in patients with Crohn's disease unresponsive to anti-TNFα therapy

Abstract: Our results show that anti-TNFα therapy significantly downregulates a subset of inflammatory genes even in patients who fail to achieve endoscopic remission, suggesting that these genes may not be dominant in driving inflammation in non-responders. On the other hand, we identified IL1B and IL17A as genes that remained altered in non-responders, pointing to potentially more relevant targets for modulating mucosal damage in refractory patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 41 publications
7
90
1
8
Order By: Relevance
“…Interestingly, we found that expression of miR-301a was found to be markedly decreased in the inflamed mucosa of patients with CD from the remission and response groups after IFX induction therapy compared with that before IFX therapy, while no change in miR-301a expression was observed in the failure group (figure 2B, and see online supplementary figure S1A,C,D). Interestingly, a recent report has shown that some pro-inflammatory cytokines such as IL-6 were also downregulated even in patients with CD who did not respond to IFX therapy 29. Since we showed that in vitro stimulation with IL-6 was able to modestly induce miR-301a expression on CD4+ T cells, their findings suggest that IL-6 may be dispensable in miR-301a expression in vivo.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, we found that expression of miR-301a was found to be markedly decreased in the inflamed mucosa of patients with CD from the remission and response groups after IFX induction therapy compared with that before IFX therapy, while no change in miR-301a expression was observed in the failure group (figure 2B, and see online supplementary figure S1A,C,D). Interestingly, a recent report has shown that some pro-inflammatory cytokines such as IL-6 were also downregulated even in patients with CD who did not respond to IFX therapy 29. Since we showed that in vitro stimulation with IL-6 was able to modestly induce miR-301a expression on CD4+ T cells, their findings suggest that IL-6 may be dispensable in miR-301a expression in vivo.…”
Section: Resultssupporting
confidence: 54%
“…Clinical remission was defined as a CDAI score of <150 points, and clinical response as a decrease in the CDAI score ≥70 points at the evaluation time point in comparison with the baseline index. The failure category included all the remaining patients, whose CDAI was not significantly changed or increased 20 28 29. Endoscopic response to IFX therapy was also assessed at week 12 after initial administration and endoscopic variables were scored according to the Simple Endoscopic Severity for CD (SES-CD) as described elsewhere 30 31.…”
Section: Methodsmentioning
confidence: 99%
“…However, in CD, Leal et al 16 showed by whole-genome transcriptional analysis in colonic mucosa that anti-TNF therapy downregulates a subset of inflammatory genes even in patients who do not achieve endoscopic remission.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, optimize the dose is a strategy to regain response to the anti-TNF, as increase the dose (Infliximab -10mg/kg) or decrease the interval between infusions (Infliximab every 4 weeks and Adalimumab 40 mg weekly), before you consider replacing the biological (1) . The chance for another class of therapy is a stated strategy in cases of lack of response to therapy optimization and high levels of circulating antibodies against anti-TNF (1,25,32) . Although, there are no available testes for measure the drug level, neither the detection of antibodies anti-drugs in Brazil, the optimization has been done empirically.…”
Section: Biological Therapymentioning
confidence: 99%